Improve the scalability and performance of fault-tolerant for failable stability routing in networks connection - Taha Jebur, Zainab; Khalil Ibrahim, Sura (International Journal of Engineering and Technology, 2019)
Practically, the execution of fault-tolerant routing dependent on the reservation of system assets is generally connected with a decline in general execution and versatility of convention arrangements. In such manner, a spilling model has been recommended that is centered around expanding the versatility and execution of fault-tolerant routing arrangements. The structure of the model incorporates conditions that are in charge of the way that the principle and reinforcement courses vary just in those system components for which the reservation is composed. This is reflected in the change of the objective function in the formulation and solution of the optimization problem of fault-tolerant routing. The given numerical examples confirmed the effectiveness of the proposed solution.
Keywords: Flow; Model; Fault Tolerance; Routing; Scheme; Redundancy.